2021
DOI: 10.1097/bsd.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Social Media Use Among Active American Members of the Cervical Spine Research Society

Abstract: Objectives: The objectives of this study are (1) to quantify social media use among active American Cervical Spine Research Society (CSRS) members; (2) to determine if there is an association between practice setting, region, or years of active membership and social media use. Summary of Background Data:Many patients now seek health and physician information online, including on social media. Indeed, social media use by orthopedic surgeons has been shown to be associated with more and improved ratings on physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…Consistent with prior studies on social media usage, LinkedIn was the most frequently reported social media platform utilized, with 56.1% of the sports medicine surgeons included in our study having a LinkedIn account. Bernstein et al 3 performed a similar analysis of CSRS members and found that 56% of surgeons had a LinkedIn account, while Narain et al 14 similarly reported that 61% of shoulder and elbow surgeons had a LinkedIn account. Lander et al 12 reported a slightly lower presence on LinkedIn (36.8%) among fellowship-trained pediatric orthopaedic surgeons; however, LinkedIn was still the most popular platform reported after professional webpages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with prior studies on social media usage, LinkedIn was the most frequently reported social media platform utilized, with 56.1% of the sports medicine surgeons included in our study having a LinkedIn account. Bernstein et al 3 performed a similar analysis of CSRS members and found that 56% of surgeons had a LinkedIn account, while Narain et al 14 similarly reported that 61% of shoulder and elbow surgeons had a LinkedIn account. Lander et al 12 reported a slightly lower presence on LinkedIn (36.8%) among fellowship-trained pediatric orthopaedic surgeons; however, LinkedIn was still the most popular platform reported after professional webpages.…”
Section: Discussionmentioning
confidence: 99%
“…However, these differences in the social media presence between academic and private practice surgeons were not observed in the previous literature on CSRS members or shoulder and elbow surgeons. 3 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Donnally et al, 3 it was found that spine surgeons who have a social media account (eg, Instagram, Facebook) are more likely to have higher online review scores. For Cervical Spine Research Society (CSRS) surgeons in particular, Benstein et al 5 saw that the majority of members have a professional website or LinkedIn, although less utilize social media platforms (ie, Instagram; 3.2%). Thus, increasing the social media presence among CSRS members may be a worthwhile endeavor.…”
mentioning
confidence: 99%